The Role Of The Islamic Empire In The Development Of Islamic Education In Indonesia - Isthifa Kemal (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to analyze the role of Islamic Empires in the development of Islamic education in Indonesia. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible pages such as Google Scholar and SINTA. Then the data were analyzed and checked for validity through data triangulation. The results of this study concluded that the role of the Islamic kingdom in the development of Islamic education in Indonesia was to influence the process of Islamization in Indonesia through the establishment of various educational institutions, such as (1) Aceh (Darussalam, Pasai and Malacca), establishing Balai Setia Hukama, Balai Setia Ulama, and the Ulama Association Congregation Hall; (2) Mataram Kingdom, establishing grand mosques in each district as well as mosques for each village, combining cultural elements with the principles of Islamic teachings, and classifying the levels of recitation in Islamic boarding schools starting from the level of the Koran, recitation of turat books, large Islamic boarding schools , and level of special expertise or specialty; and (3) the Islamic kingdom of Malacca, the palaces and houses of preachers to become Islamic educational institutions, as well as the use of mosques and surau as Islamic educational institutions.